Kemajuan dan Pengembangan Drone pada Sektor Konstruksi di Indonesia - Putri Ilmi Sakinah; Yongki Alexander Tanne; Fatwa Ibnu Isa; Muhamad Haikal Hegemur (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
The use of drones is growing along with advances in technology. Initially, drones were used for military purposes, but now drones have penetrated the construction sector and offer various benefits, especially in the information retrieval process. For this reason, this research tries to qualitatively obtain an overview of the progress of drone use in Indonesia based on a comparison of literature studies and case studies on the X Hospital Development Project while at the same time looking at its development potential. Based on the project life cycle (PLC), the use of drones in Indonesia includes the project planning stage; project drafting and design; to construction planning and supervision. Compared to these developments, drones in the X Hospital Construction Project are used in the construction supervision stage only. This shows the great potential that is still hidden from the use of construction drones to improve the quality of the construction sector. Furthermore, the development direction for the use of drone technology will be maximized and provide added value if integrated with other technologies such as Cloud and Building Information Modeling (BIM). This research is expected to be an overview of the development of construction projects in adopting and utilizing technology to improve the quality of project implementation and overcome construction project problems in Indonesia, specifically the use of drone technology. Keywords—drone, construction, project life cycle, monitoring, case study